Analysis of palemahan application on tourist attraction and waste conditions in a tourism city - Jayanthi, Luh De Dwi (Journal of Sustainability, Society, and Eco-Welfare, 2025)
Background: Denpasar City, as a prominent tourism hub in Bali, faces significant urban environmental challenges due to rapid land conversion, increasing population, and growing tourism activities. In 2023, Denpasar produced the highest volume of waste in Bali, reaching 357,985.69 tons/year, reflecting the strain on waste management systems and environmental sustainability. Methods: This study uses a quantitative approach through spatial analysis using QGIS and literature review. The variables analyzed include land cover, population, tourist attraction (DTW) distribution, and annual waste generation across four sub-districts in Denpasar. Findings: The analysis revealed that South Denpasar has the largest area (49.89 km²), highest population (311,590 people), highest waste generation (111,080.23 tons/year), and the most tourist attraction units (28 DTWs). Despite this, it has the lowest population density compared to other sub-districts. These conditions highlight the environmental burden experienced by this region, particularly in waste management and land use pressure due to its tourism-related activities. Conclusion: The city of Denpasar faces complex challenges in achieving its vision as a sustainable Tourism City. The integration of the Balinese local wisdom value of palemahan, emphasizing harmonious human–environment relationships, is crucial to address the physical, biological, and social environmental issues arising from unregulated waste and land use. Furthermore, the dense population and high tourism activity call for future research on their impact on water and air quality. Novelty/Originality of this article: This study offers a spatially grounded analysis of the interrelation between tourism, population pressure, and waste generation in Denpasar. It uniquely incorporates traditional environmental values (palemahan) as a cultural approach to addressing urban ecological challenges.